Sikap Positif Mahasiswa Terhadap Penggunaan Bahasa Indonesia dalam Lingkungan Kampus STKIP PGRI Pacitan - Hendriyanto, Agoes; Sutopo, Bakti; Apriyani, Catur (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The purpose of this research was to understand the forms of language attitudes and the factors influencing the language attitudes of students at STKIP PGRI Pacitan towards the Indonesian language. The approach used was descriptive qualitative. Data collection methods in this research included observation, questionnaires, and interviews. The data analysis method used Miles and Huberman's analysis method, which involved data reduction, data presentation, and drawing conclusions. The results of the study showed that the majority of students in the STKIP PGRI Pacitan campus (93%) exhibited loyalty and pride in using the Indonesian language in various aspects, including communication on social media, entertainment, and daily interactions. They were aware of the importance of the Indonesian language in maintaining national unity and considered it attractive and sustainable in the era of globalization. This positive attitude was influenced by factors such as students' knowledge and experiences, a supportive campus environment, emotional aspects as Indonesian citizens, the influence of mass media, and the role of educational institutions. In this increasingly advanced digital era, it is important to continuously enhance understanding, create a supportive environment, and provide resources that promote the use of proper and good Indonesian language to maintain this positive attitude consistently.